Discrete and Polymeric Organometallic‐Organic Hybrid Materials Based on the Diphosphorus Complex [Cp2Mo2(CO)4(η2‐P2)], CuI Salts, and 2, 2′‐Bipyrimidine. Issue 47 (20th December 2017) - Elsayed Moussa, Mehdi; Attenberger, Bianca; Seidl, Michael; Schreiner, Anderea; Scheer, Manfred
Abstract : The reaction of the diphosphorus complex [Cp2 Mo2 (CO)4 (η 2 ‐P2 )] (1 ), with the Cu I salts [Cu(CH3 CN)4 ][BF4 ] or [Cu(CH3 CN)4 ][PF6 ], and a mixture of [Cu(CH3 CN)4 ][BF4 ] and CuCl in the presence of 2, 2′‐bipyrimidine (2 ) is studied. Depending on the Cu I salts used and the layering solvent involved in the crystallisation, a variety of novel coordination compounds are accessible in moderate to excellent yields (26–80 %): the novel dicationic molecular organometallic‐organic hybrid complexes [{Cp2 Mo2 (CO)4 (µ3, η 1:2:2 ‐P2 )}4 (µ2, η 1:1:1:1 ‐C8 H6 N4 )Cu2 ][BF4 ]2 (3 ) and [{Cp2 Mo2 (CO)4 (µ3, η 1:2:2 ‐P2 )}2 {Cp2 Mo2 (CO)4 (µ3, η 2:2:2 ‐P2 )}2 (µ2, η 1:1:1:1 ‐C8 H6 N4 )Cu2 ][PF6 ]2 (4 ), the unique neutral 1D organometallic‐organic hybrid polymer [{Cp2 Mo2 (CO)4 (µ4, η 1:1:2:2 ‐P2 )}2 (µ2, η 1:1:1:1 ‐C8 N6 N4 )(CuCl)2 ] n (5 ) and the unprecedented 2D organometallic‐organic hybrid polymer [{Cp2 Mo2 (CO)4 (µ4, η 1:1:2:2 ‐P2 )}(µ2, η 1:1:1:1 ‐C8 H6 N4 ){Cu2 (µ‐Cl)}]2 [BF4 ]2 n (6 ). Abstract : The reaction of the diphosphorus complex [Cp2 Mo2 (CO)4 (η 2 ‐P2 )] (Cp = C5 H5 ) with different copper(I) salts and 2, 2′‐bipyrimidine afforded four new coordination compounds: two novel cationic organometallic‐organic complexes, one cationic 2D hybrid polymer, and the first neutral 1D organometallic‐organic hybrid polymer.